Washing 'Dirty Work' in Academia and Beyond: Resisting Stigma as an Early Career Researcher Investigating Sexuality in the Digital - Chiara Perin (Gender a Výzkum)
During my PhD studies, my ethnography of the r/NoFap subreddit involved grappling with challenges that questioned my research design, academic posture, political stance, gender identity, sexuality and desire and asked for mutable choices to deal with them. With over 1.1 million members, predominantly men, this Reddit channel advocates abstinence from pornography consumption and excessive masturbation as a means to overcome a self-diagnosed porn addiction, porn overuse, and compulsive sexual behaviour. The related conversations are dominated by evolutionary narratives on gender and sexuality, men's sexual entitlement to women, and the heteronormative coital encounter as an imperative. Academic literature has identiﬁed heterosexist, patriarchal, and misogynistic discourses in the community (Prause, Ley 2023; Burnett 2021; Hartmann 2020; Taylor, Jackson 2018). My ethnographic journey demanded substantial emotional labour as I navigated potentially toxic technocultures (Massanari 2015) and non-sex-positive environments. What I had not foreseen was the systematic stigma, discomfort, and delegitimisation in both institutional (academic) and non-institutional contexts (social and familial). This paper provides a detailed account of these experiences, shedding light on the personal, institutional, and emotional struggles inherent in gender and sexuality scholarship as a result of the pervasive stigma and delegitimisation. This account aims to shed light on the consequences of doing 'dirty work' and suggest strategies of personal resistance, with the awareness that transformative actions cannot be merely individual but are necessarily structural and collective.